log(5x+1)=1.2

Simple and best practice solution for log(5x+1)=1.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(5x+1)=1.2 equation:


Simplifying
log(5x + 1) = 1.2

Reorder the terms:
glo(1 + 5x) = 1.2
(1 * glo + 5x * glo) = 1.2
(1glo + 5glox) = 1.2

Solving
1glo + 5glox = 1.2

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Reorder the terms:
-1.2 + 1glo + 5glox = 1.2 + -1.2

Combine like terms: 1.2 + -1.2 = 0.0
-1.2 + 1glo + 5glox = 0.0

The solution to this equation could not be determined.

See similar equations:

| y8/y3 | | 6+k^7=-2 | | 3x^3-5x-1=0 | | (36x^4+9)=0 | | 0.05(0.3x-0.06)= | | logx^729=3 | | 4n+5=2n+8 | | logx^36=2 | | 4y+49=27y+7 | | 4y+36=27y+7 | | 4.8x-4=4(1.2x-1) | | 4y+1636=27y+7 | | 8x-5x=x+8 | | 4y+25=27y+7 | | 4y+16=27y+7 | | y+2.4=7.33 | | 8+3n-5=9n+9-5 | | 2[2(3x-1)+3]-2(2x+5)=2(3x-3) | | 4+t^3=-3 | | s*6-43=83 | | 1+25=2x+20 | | 2[2(8x-1)+3]-2(2x+5)=2(3x-3) | | 2[2(83x-1)+3]-2(2x+5)=2(3x-3) | | 5x-1=19x | | 4a+19b-12a-10b= | | y=25+.57x | | 22x=16 | | 4(2a-1)-7a=4 | | b^2-2=8 | | 5(y-2)=45 | | 3/5x^2=75 | | 3(4v+1)-3(2v+3)=2(v-7)+4 |

Equations solver categories